Cognitive Behavior Therapy for Depression (Journal Of Educational and Psychological Researches, 2022)
The current research aimed to identify the cognitive-behavioral therapy on people with depression, through the following hypothesis (there are no statistically significant differences in the sample before and after cognitive-behavioral therapy). The importance of research is highlighted through the use of cognitive-behavioral therapy, to be used in treating depression, anxiety and fears by health institutions. It is also considered as a reference for psychological studies related to this topic to be added to our libraries that already suffer from a scarcity of this type of resources. The cognitive-behavioral therapy was used in the treatment of five male subjects.The study revealed the existence of statistically significant differences, which proves the success of this method. The study concluded the effectiveness of cognitive-behavioral therapy in reducing symptoms of depression. The study recommended adopting this method of treatment and suggested conducting studies on a larger sample.